Technological Advances and Evolution of Biowarfare: A Threat to Public Health and Security - Jha, Ashima (KnE Social Sciences, 2023)
Research in public health and medical sciences has always placed a high priority in managing disease outbreaks, effective treatment capacities, and overall human health and wellbeing. Despite the fact that advances in biology, biotechnology, and medical research have proven to have sufficient value in terms of lifesaving treatments, these have also presented major challenges in their effective utilization. Hence, potentially posing serious risks in the form of bioweapons, thereby, endangering governance frameworks that prioritize biosecurity and counter-biological warfare. In this review paper, a thorough literature review has been conducted to explore the critical aspects between advances in biology and their potential misuse, which could result in serious risks to public health and security. The history of biowarfare has been studied, and the results identify major criteria that have been used in deeming a biological agent fit for the use in mass destruction programs. Five historical biological warfare agents (Bacillus anthracis, smallpox, Yersinia pestis, Vibrio cholerae, and Francisella tularensis) have been studied critically to conclude that not all biological agents may act as bioweapons, but only those agents meeting these criteria may cause catastrophic damage. This paper examines key risks associated with bioweaponry posed by the convergence of biotechnology and artificial intelligence as evident in today’s world of innovation. Based on the situational analysis of the COVID-19 pandemic, the author also discusses some of the major shortcomings of the international framework and the healthcare system in handling future biological attacks having the potential of mass destruction. Through this paper, associations between different stakeholders, scientific communities, and research groups are highly recommended along with identifying the problem at its roots. Keywords: bioweapons, biological toxin, biotechnology, artificial intelligence